(untitled) (The Research of Medical Science Review, 2025)
Background: Obstetric hemorrhage can cause severe complication but it could be preventable. A key factor in lowering mortality and morbidity associated with C-sections is the early detection of blood loss and timely management. The mean pre and post-op hemoglobin level is an indicator of blood loss in patients undergoing Caesarian section. Methodology: It was a Quasi Experimental study, conducted in department of Gynecology and Obstetrics Saidu Group of teaching Hospital (SGTH) Swat. It was a six-month study and data collection were started after the approval from CPSP Pakistan. Sample size was calculated using open epi.com software Data was collected using Written proforma through non-probability sampling technique. Results: The study of 60 patients (mean age 28.54 ± 1.32 years) found mean operation time was 44.08 ± 7.91 minutes and mean intraoperative blood loss was 660 ± 86 ml, with no significant differences between age groups. Mean pre- and post-operative hemoglobin levels were 11.59 ± 1.01 g/dl and 9.85 ± 0.14 g/dl, respectively (paired t-test p = 0.0003). There was a significant negative correlation between intraoperative blood loss and drop in post-op hemoglobin (r = -0.45, p < 0.05). Conclusion: Our study concludes that older patients (34-40 years) tended to have higher blood loss and lower postoperative hemoglobin levels (9.85±0.14 g/dl) compared to younger groups. Overall hemoglobin drop (1.74 g/dl) after C-section was clinically significant, showing a direct relationship between increased blood loss and lower postoperative hemoglobin levels. The findings suggest age may influence surgical outcomes, but larger studies are needed to confirm these trends.